The associations between specific-type sedentary behaviors and cognitive flexibility in adolescents - Cui, Jie; Li, Lin; Dong, Chao (Frontiers in Human Neuroscience, 2022)
Background: The prevalence of sedentary behavior in adolescents has aroused social attention. The association between sedentary behavior and cognitive flexibility remain unclear, and it may vary depending on the type of sedentary behavior. This study aimed to investigate the associations between specific-type sedentary behaviors and cognitive flexibility in adolescents. Method: A total of 700 Chinese adolescents aged 10 to 15 years were recruited. The self-report questionnaire was used to assess total sedentary time, entertainment screen-based sedentary time, and educational sedentary time. The More-odd shifting task was used to assess cognitive flexibility. Results: The correlation analysis showed that entertainment screen-based sedentary time was negatively correlated with cognitive flexibility, whereas educational sedentary time was positively correlated with cognitive flexibility. The regression analysis also further revealed that a significantly negative association between entertainment screen-based sedentary time and cognitive flexibility, while a significantly positive association existed between educational sedentary time and cognitive flexibility. Conclusion: The findings shown that the association between entertainment screen-based sedentary behavior and cognitive flexibility differs from educational sedentary behavior in adolescents, providing new ideas for a more comprehensive understanding of the association between sedentary behavior and cognitive flexibility in adolescents.